The Treuhandanstalt, privatization and the role of the courts - Mark K. Cassell (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
The paper considers how the Treuhandanstalt's legal identity as both a publicand private entity helps to explain the process of privatization or creation of property by the state after 1989. I argue the agency did not easily fit within the rigid categories of the German legal system. Moreover, its hybrid status limitedthe degree to which individuals or groups could make use of the courts to holdthe agency accountable. As neither a fully public nor fully private entity, the agency's status successfully circumvented a number of traditional forms ofcontrol that exist in both public and private agencies in Germany. As a result, privatization was defined in a very narrow neo-liberal sense despite what one would predict from the standard accounts of the German Model. – – In dem Papier wird der Frage nachgegangen, wie die rechtliche Konstruktion der Treuhandanstalt als einer sowohl staatlichen wie privaten Einrichtung dazuherangezogen werden kann, um den Prozeß der Privatisierung wie der Schaffung von Privateigentum durch den Staat nach 1989 zu erklären. Es wirddie Meinung vertreten, daß diese Organisationsform nur schwer in die striktenKategorien des deutschen Rechtssystems paßte. Darüberhinaus hat dieser hybride Status die Möglichkeiten für Einzel- wie für Rechtspersonen eingeschränkt, die Treuhand vor Gericht zu belangen. Als weder "richtig" staatliche noch "richtig" private Einrichtung konnten die normalerweise üblichen Formen staatlicher wie privater Kontrolle erfolgreich umgangen werden. Daraus ist zufolgern, daß die Privatisierung - im Gegensatz zu den Standards des "Modell Deutschland" - in einem engen neoliberalen Sinne verstanden und praktiziert wurde.
Keywords: 330; Privatisierung; Justiz; Public Choice; Neue Bundesländer